HUBUNGAN INTENSITAS MENONTON TIKTOK NARASI DENGAN TINGKAT PENGETAHUAN POLITIK GENERASI Z - Ana Nurlaili Dwi Aprilia; Sari, Maya Mustika Kartika (Kajian Moral dan Kewarganegaraan, 2024)
Generation Z, who grew up with technology, is deeply engaged with social media, including TikTok, which has become a vital platform for disseminating political information. The TikTok account "Narasi," founded by Najwa Shihab, captures their attention with content on politics, law, social issues, and inspirational stories. According to the uses and effects theory, the intensity of media consumption can influence knowledge, attitudes, and perceptions of social reality. This study employs a quantitative approach with a correlational design to examine the relationship between the intensity of watching TikTok Narasi and the level of political knowledge among Generation Z. Data were collected through an online questionnaire from 108 respondents who follow TikTok Narasi. Data analysis using Spearman's Rho correlation test showed a significance value of 0.00, indicating a significant relationship between the intensity of watching TikTok Narasi and political knowledge regarding the 2024 election. The correlation coefficient of 0.654 indicates a strong, positive, and direct relationship between these variables. The results suggest that there is a significant relationship between the intensity of watching TikTok Narasi and the level of political knowledge among Generation Z. The higher the intensity of watching TikTok Narasi, the greater the political knowledge of Generation Z about the 2024 presidential and vice-presidential candidates. Keywords: Intensity, TikTok, Political Knowledge, Generation Z.